The nexus between the digital divide and social cohesion and their socio-economic drivers in South Africa - Magida, Ayanda (University of the Witwatersrand, Johannesburg, 2023)
The study aimed to achieve two objectives. Firstly, it sought to investigate the correlation between the digital divide and social cohesion in South Africa. Secondly, it aimed to evaluate the socio-economic factors contributing to the digital divide and attaining social cohesion. The study used ecological systems theory as the primary theory to underpin its research. Social categorisation and resource appropriation theories were employed as secondary theories to enhance understanding of social cohesion and the digital divide, respectively. A concurrent mixed-method design incorporating quantitative and qualitative methods was utilised to gather comprehensive data. The quantitative data was acquired through online and paper-based surveys, while in-depth interviews were conducted to obtain qualitative data. Using the Qualtrics data collection platform, the online survey was distributed through various channels and platforms, including social media, using convenience sampling. Fieldwork in three semi-urban areas in Gauteng was conducted to carry out the paper-based survey. A total of n=1140 surveys were completed, and after data cleaning, n=857 respondents were included in the final analysis using SPSS. The quantitative data collected from the survey was analysed using descriptive statistics, structural equation modelling, and regressions. Meanwhile, the qualitative phase involved purposively selecting twelve participants for an interview, with the transcripts being analysed using thematic analysis and NVivo. Eight themes were identified through a hybrid data analysis approach combining inductive and deductive approaches. Results from the quantitative phase indicate a correlation between social cohesion and the digital divide. Socio-economic factors such as age, geographic location, and population group drive social cohesion. Similarly, age, education level, and gender influence internet access: socio-economic factors, population group, geographic location, education level, and economic activity impact internet usage. Lastly, the advantages of being online are influenced by socio-economic factors such as age, education level, and economic activity. Nine themes emerged from the qualitative analysis through an inductive and deductive approach. Participants expressed shared definitions and understandings of the digital divide and identified iii its drivers, which encompassed infrastructure, affordability, electricity, and literacy levels. Regarding social cohesion, the participants expressed that the notion of a "rainbow nation" is a myth, and socio-political factors act as barriers to achieving social cohesion. The research indicates that the digital divide significantly impacts social cohesion in South Africa. However, it is important to recognise that social cohesion and the digital divide are complex issues influenced by various factors, such as socio- economic status, race, culture, and historical context. Therefore, exploring and addressing other obstacles that prevent the country from achieving social cohesion and bridging the digital divide is vital. The report has significantly contributed to several empirical, methodological, and practical areas. The study has provided valuable insights into the digital divide, social cohesion, and socio-economic drivers, contributing to our understanding of these complex issues. The research has enriched our understanding of the digital divide and social cohesion by adopting a comprehensive approach that captures a range of perspectives and provides nuanced insights. Additionally, using both quantitative and qualitative data has enhanced the validity and rigour of the findings. Ultimately, the study's practical contributions are especially noteworthy given that social cohesion is a crucial pillar of South Africa's democratic project. Understanding the factors that hinder its attainment is essential, and this research sheds light on micro and macro factors contributing to achieving social cohesion.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in the Faculty of Commerce, Law and Management,Wits Business School, University of the Witwatersrand Johannesburg July 2023
Keywords: UCTD; Digital divide; social cohesion; South Africa; socio-economic factors; Ecological systems theory; resources appropriation theory; social categorisation theory; concurrent mixed method; SDG-8: Decent work and economic growth